2007
DOI: 10.1111/j.1467-9566.2007.01029.x
|View full text |Cite
|
Sign up to set email alerts
|

Bodies, mothers and identities: rethinking obesity and the BMI

Abstract: Despite the intense level of attention directed towards obesity, there has been limited success in addressing the rising rates of this public health phenomenon. This paper argues that current approaches to obesity fail to consider concepts of embodiment, and in particular, that gendered and class-based experiences of embodiment are ignored in health promotion practices and policies. Drawing on Bourdieu's concept of habitus , this ethnographic study sought to locate obesity within the biographies and everyday e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
131
2
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(143 citation statements)
references
References 36 publications
6
131
2
4
Order By: Relevance
“…These findings resonate with the work of Warin et al (2008) who identified the difficulty of acting on health promotion initiatives as a mother on low income; in their study, the participants' relational identity as mothers required them to displace their individual needs for the sake of their children. For instance, JulieAnne, a 21-year-old mother of three young children, explained how the care for her children shifted her priorities by setting aside her personal investments in health.…”
Section: Motherhood and Its Prioritiesmentioning
confidence: 62%
See 1 more Smart Citation
“…These findings resonate with the work of Warin et al (2008) who identified the difficulty of acting on health promotion initiatives as a mother on low income; in their study, the participants' relational identity as mothers required them to displace their individual needs for the sake of their children. For instance, JulieAnne, a 21-year-old mother of three young children, explained how the care for her children shifted her priorities by setting aside her personal investments in health.…”
Section: Motherhood and Its Prioritiesmentioning
confidence: 62%
“…Very little sociocultural research has applied qualitative methodologies to focus on contextual factors influencing the uptake of health practices related to body weight for underprivileged women. One notable exception is the work of Warin et al (2008) who located obesity within the lived experiences of two groups of Australian women of differing socio-economic contexts (low and middle/upper class), and found that gender and social class, as well as their role as mothers, played a central role in their participants' health practices as well as their constructions of identity.…”
Section: Women Lifestyle and Obesity A Critical Approachmentioning
confidence: 99%
“…Some authors [33,34] suggest mothers breastfeed because they are socio-culturally deemed responsible for meeting all of their children's needs. Thus they strive to follow the recommended biomedical guidelines to minimise potential health risks and achieve the social status of a "good mother" [35].…”
Section: Exploring Perceptions and Practices Of Biomedical Norms Durimentioning
confidence: 99%
“…The dominant construction of childhood as passive, unable or unwilling to take responsibility for their own health/behaviour, means that they do not easily fit within the neoliberal model of individualised embodiment on which this approach is based. Since children 'do not qualify as full liberal subjects' (Maher et al, 2010, 235) they are therefore, at best viewed as possible vectors to carry information on 'healthy lifestyles' from educational spaces back to more responsible actors within the home (parents) or, more commonly, are conceptualised as incapable of acting responsibly, as the cause of irresponsible behaviours (as in the case of 'pester power') (Colls and Evans B, 2008) or their ill-health is blamed on inadequate parenting, usually mothers (see Warin et al, 2008). …”
Section: The Embodied-subject In Health Pedagogiesmentioning
confidence: 99%